Pola Kegagalan Balok Beton Bertulang Spiral Tanpa Beton Pada Penampang Tarik - Astiah Amir; Aulia Rahman; Yulita Rahmi; Veranita Veranita; Dewi Purnamasari (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
Abstract The exploration of natural materials to produce concrete has an impact on environmental conditions and global warming that can cause natural disasters. Therefore, the use of concrete materials must be as efficient as possible. One solution to overcome this problem is to reduce the concrete in the tensile area and strengthen the beam using steel reinforcement in the support area. This study aims to determine the effect of tensile reinforcement on the behavior of beams without concrete in the tension area using a spiral system on crack patterns and beam patterns. The method used was an experimental method by making 2(two)specimens, a normal concrete beam (BN) as a control beam, and a spiral concrete beam without reinforcement in the tensile section with the addition of experimental reinforcement at the support section (BTRS 60D) where D is the diameter of the main reinforcement. The beams were designed as normal quality concrete beams with concrete quality of 45.07 MPa at the testing age of 28 days. The beam's dimension was 150 mm x 200 mm x 3100 mm. This study obtained the ultimate load on the BTRS specimen of 35.1 kN. While on the BN specimen, the ultimate load reached 47.65 kN. There was a decrease in BTRS service load by 27.57%. It is observed that the BN specimen experienced flexural cracks. The beam failure of the 2 test objects experienced beam failure that resembled under-reinforced where the reinforcing steel melted before the concrete was crushed. Keywords: spiral reinforcement, failure pattern, crack pattern.